The Effectiveness of the Cigarette Tax Earmarking Policy for Healthcare Financing in Indonesia: A Systematic Literature Review - Mohamad Djasuli; Fatimatus Zahra; Isnanda Fitri Maulidina (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Optimizing cigarette tax earmarking is important as a fiscal instrument to support healthcare financing and strengthen Regional Original Revenue (Pendapatan Asli Daerah [PAD]) in Indonesia. Although this policy has been normatively regulated through various legal frameworks, its regional implementation continues to face challenges, including ineffective fund utilization, weak supervision, and limited transparency and accountability in budget management. This study aims to analyze the contribution of cigarette tax to regional revenue and evaluate the effectiveness of cigarette tax earmarking in supporting healthcare financing in Indonesia. A qualitative approach using the Systematic Literature Review (SLR) method was employed. Data were collected from relevant national and international scientific journal articles indexed in Google Scholar, SINTA, and Garuda. The literature selection process followed the PRISMA framework through identification, screening, eligibility assessment, and inclusion stages. Based on this process, 15 articles met the inclusion criteria and were analyzed using a descriptive-analytical approach. The findings indicate that cigarette tax contributes significantly to regional revenue and has substantial potential to support healthcare financing through an earmarking mechanism. However, policy implementation remains suboptimal because of a persistent gap between regulatory design and practical execution. Major obstacles include low tax revenue realization, inappropriate budget allocation, weak monitoring systems, and disparities in regional governance capacity. The study concludes that cigarette tax earmarking in Indonesia is normatively sound but operationally weak, requiring stronger supervision, transparency, and accountability in fund management. This study contributes to public finance and health policy literature by clarifying the fiscal role and implementation constraints of cigarette tax earmarking, while its practical implications emphasize the need to improve regional fiscal governance to strengthen healthcare financing and regional fiscal autonomy.